Identifikasi Mekanisme Kedalaman Gempa Vulkanik Gunungapi Soputan Menggunakan Data Seismik Vulkanik Dalam Periode April-Mei 2014 - Sriwahyu Tiyow; Patricia Silangen; Theresje Mandang (Jurnal FisTa : Fisika dan Terapannya, 2022)
Indonesian An archipelago country that has many volcanoes, namely 147 volcanoes 127 of which are active volcanoes. Spread in several regions of Indonesian following the boundaries of the active plate starting from the islands of Sumatra, Java, Bali, West Nusa Tenggara, Flores, Sulawesi and Maluku. Soputan volcano is one of 127 active volcanoes in Indonesia, is a Strato volcano. As an active tecto-volcanic country, with many volcanoes we try to minimize and prevent the dangers posed by volcanic eruptions. Based on these thoughts, to date in Indonesian various methods of volcanic natural disasters have been carried out, including earthquakes (seismic). Volcanic earthquakes usually occur in the area around volcanoes and their magnitudes are generally very small, averaging less than 5 on the Richter Scale. The depth of the volcanic earthquake ranges from 0-40 km. Based on the hypocentrum distribution of the depth of the epicenter, it shows that the earthquake point that occurred before the eruption was at a depth of 0 km - 2 km at sea level, while the point of the earthquake that occurred during the eruption was at a depth of 0 km - 2 km below sea level, the point of the earthquake that occurred after the eruption it is at a depth of 0 km - 3 km below sea level. The mechanism for the eruption of Mount Soputan Volcano is a visual change in the vegetation around the crater, the plants turn yellow and can die, as soon as the thin crater turns gray.